PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU DENGAN PEMBERIAN PUPUK DAN MULSA - Rosianti Mokoginta; Muhardi Muhardi; Muhd Nur Sangadji (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research aimed to study the effect of the combination of inorganic fertilizers, organic fertilizers and rice straw mulch on growth and yield of LembahPalu shallot variety. This study was conducted in farmers’ fields in Makuvillage of Sigi districtin May to July 2013 using a randomized block design (RBD).Treatmentswere a combination of different inorganicfertilizers, organic fertilizers and rice straw mulch consisting of seven treatments (A= onion cultivation methods applied by farmers, B= inorganic fertilizer, C= organic fertilizer, D= inorganic fertilizer + organic fertilizer, E= inorganic fertilizer + rice straw mulch, F= organic fertilizer + rice straw mulch and G= inorganic fertilizer + organic fertilizer + rice straw mulch).Each treatment was replicated infour groups so that there were 28 treatment units. Differences between treatmentswere analyzed using the honest significant (HSD) test at 5% level. The B treatment (inorganic fertilizer) showed better plant growth components while the G treatment (inorganic fertilizer + organic fertilizer + rice straw mulch) had better yield components.Keywords : Anorganic fertilizer, Onion, Organic, Rice Straw Mulch